Web-Based Menu Ordering Information System using QR Code with Waterfall Method at Bravura Café - Suherman; Shelly Octaviani; Irfan Afriantoro (Jurnal Teknologi Informatika dan Komputer, 2026)
Today's society tends to want things to be fast and efficient, for example, when ordering food or drinks at a cafe. In business, customer satisfaction and quality service are crucial. Therefore, a solution or idea emerged that could simplify ordering through the use and assistance of QR code technology. Menu ordering at Bravura Cafe is still done manually. It can be seen from the recording of transactions that still use sheets of paper, as well as ineffective ordering activities. This causes employees to be quite overwhelmed when the cafe is busy, this can also hamper the performance and quality of service at Bravura cafe. QR code is a system that uses a two-dimensional image code which also comes from the evolution of Barcode. The use of QR codes is very common in many countries. This is because of its ability to store more data than a barcode so that it is able to encode information in various languages. In this study, the research method used is the waterfall method. The design method uses unified modeling (UML). The analysis carried out includes analysis of the current system and analysis of the proposed system. The results of this study are a web-based menu ordering information system using a QR Code with the waterfall method. The author hopes that this system will be useful in facilitating the work of employees and improving service quality.